2018
DOI: 10.1101/492330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Adherence to Antiretroviral Therapy Among Adult People Living with HIV/AIDS in North East, Ethiopia

Abstract: Back ground:The scale-up of anti retroviral treatment is among the greatest successes of the global Acquired Immunodeficiency Syndromes (AIDS) response to date and it is on a Fast-Track-approach. To contribute to the global and local target of HIV /AIDS response as well as to obtain full benefits of ART medication, strong adherence of ≥95% to Anti-Retroviral Therapy (ART) is needed. Methods:A cross-sectional study among 352 and 20 study participants for quantitative and for in-depth interview respectively. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This finding is not in line with a study conducted in northeast Ethiopia, in which there was no significant association between WHO clinical staging and adherence status. 36 The study also found that patients with a current CD4 category greater than or equal to 500 cells/mm 3 were five times more adherent than those with CD4 of below 200 cells/mm 3 . This is supported by other studies, which found that strict adherence can bring about immune reconstitution and rebuilding.…”
Section: Discussionmentioning
confidence: 79%
“…This finding is not in line with a study conducted in northeast Ethiopia, in which there was no significant association between WHO clinical staging and adherence status. 36 The study also found that patients with a current CD4 category greater than or equal to 500 cells/mm 3 were five times more adherent than those with CD4 of below 200 cells/mm 3 . This is supported by other studies, which found that strict adherence can bring about immune reconstitution and rebuilding.…”
Section: Discussionmentioning
confidence: 79%
“…The optimal ART adherence level found from this study result for study participants on a routine schedule (74.3%) is consistent with the results of a study done in Yirgalem hospital in 2009, which was 74.2%, 12 in Cape Coast metropolis, Ghana in 2018 which was 79.5% 20 and in behavioral disease counseling center, Iran in 2019 which was 75.4%. 46 However, it is lower than the study findings in Bale Robe Hospital of 2014, which was 83.1%, 21 DebreBerhan Keble Health Centre and DebreBerhan Referral Hospital of 2018 which was 87.2%, 22 Kathmandu District in Nepal of 2014, which was 86.7%, 23 and University of Gondar Referral Hospital of 2014, which was 88.2% 24 and higher than the study findings in Embu teaching and referral hospital comprehensive care clinic of 2016 which was 48.2% 25 and Embe Hospital of 2016 which was 48.2%. 26…”
Section: Discussionmentioning
confidence: 64%
“…With regard to the age of the patients, patients in the age groups 30-34, 35-39, 45-49 and 50+ years old, their odds of having good adherence compared with those who had fair and poor adherences combined were 1.54, 1.47, 1.87 and 1.68 times higher keeping all the other variables in the model constant. Studies from Gondar, Northwest Ethiopia, 23 Northeast Ethiopia 25 and Gobba Hospital, Southeast Ethiopia 20 reported that age has no significant associations with adherences. However, a study from Kenya had found that adherence to ART increased with increased age and decreased as the age goes beyond 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, studies from Gobba Hospital, Southeast Ethiopia and Northeast Ethiopia have shown that gender was not significantly associated with ART adherence. 20,25 The reason why males were prone to viral non-suppression might be due to low health-seeking behavior. [32][33][34] Compared to females, males were more likely to forgo ART because of side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation